2003
DOI: 10.1016/s1535-6108(03)00058-8
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the extracellular matrix through overexpression of collagen VI contributes to cisplatin resistance in ovarian cancer cells

Abstract: The mechanisms of drug resistance in cancer are poorly understood. Serial analysis of gene expression (SAGE) profiling of cisplatin-resistant and sensitive cells revealed many differentially expressed genes. Remarkably, many ECM genes were elevated in cisplatin-resistant cells. COL6A3 was one of the most highly upregulated genes, and cultivation of cisplatin-sensitive cells in the presence of collagen VI protein promoted resistance in vitro. Staining of ovarian tumors with collagen VI antibodies confirmed coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
249
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(257 citation statements)
references
References 32 publications
7
249
0
1
Order By: Relevance
“…GJA1, a gene encoding a gap junction protein (Cx43), was the most highly elevated gene in ACRP compared to A2780. COL11A1, HAPLN1 and PEG10, three genes previously identified by SAGE (Sherman-Baust et al, 2003) as upregulated in cisplatin resistance were also found using Agilent oligo microarrays. Genes downregulated were also identified and those decreased more than fivefold compared to A2780 are indicated in Table 2.…”
Section: Kinetics Of Gene Expression Changes: Analysis Of Downregulatmentioning
confidence: 79%
See 1 more Smart Citation
“…GJA1, a gene encoding a gap junction protein (Cx43), was the most highly elevated gene in ACRP compared to A2780. COL11A1, HAPLN1 and PEG10, three genes previously identified by SAGE (Sherman-Baust et al, 2003) as upregulated in cisplatin resistance were also found using Agilent oligo microarrays. Genes downregulated were also identified and those decreased more than fivefold compared to A2780 are indicated in Table 2.…”
Section: Kinetics Of Gene Expression Changes: Analysis Of Downregulatmentioning
confidence: 79%
“…Gene expression profiling techniques such as microarrays and serial analysis of gene expression (SAGE) have allowed the identification of genes whose expression is acutely affected by cisplatin exposure (Amundson et al, 2005;Kerley-Hamilton et al, 2005), as well as genes differentially expressed in cells that have developed cisplatin resistance (Sherman-Baust et al, 2003;Kang et al, 2004;Whiteside et al, 2004;Roberts et al, 2005;Cheng et al, 2006). In addition, these techniques have also allowed for the identification of gene expression signatures that may help predict cisplatin sensitivity in various cancers (Akervall et al, 2004;Takata et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the transcriptional ATC/PDTC profile also showed overexpression of TWIST1 and downregulation of CDH1, both important regulators of EMT in the metastatic and invasive process (Yang et al, 2004;Zavadil and Bottinger, 2005). In addition, several mesenchymal protein coding genes (members of the collagen and laminin protein families; Table 2) were overexpressed as expected for tumor invasion and angiogenesis (Sherman-Baust et al, 2003;Tang et al, 2006). An overexpression of various genes of the metalloproteinase (MMP) family was also observed (Table 2) and they have been associated with degradation of the basal lamina components, TGFb pathway upregulation and tumor invasion (Chambers and Matrisian, 1997).…”
Section: Discussionmentioning
confidence: 90%
“…Compounding these efforts are recent in vitro and in vivo data showing that aggressive melanoma cells engaged in vasculogenic mimicry are relatively unaffected by select angiogenesis inhibitors [23,24]. Additional evidence indicates that tumor cells may remodel their microenvironment with extra ECM to increase their survival in the presence of therapeutic agents [117], which has been shown to adversely affect interstitial transport in solid tumors [118]. MMP inhibitors have also experienced challenges in clinical trials, but these proteinases are still worth consideration in the development of strategies to target the tumor microenvironment [29,30,31,119].…”
Section: Discussionmentioning
confidence: 99%